Assessment of Community Relations Strategies for Rural Development in Nasarawa State and the Abuja FCT - Ugbodu, Ejeh Amina; Kente, Josiah Sabo; Akase, T. M. (Darul Yasin Al Sys, 2025)
This study assesses community relations strategies and their impact on rural development in Nasarawa State and the Federal Capital Territory (FCT), Abuja. Utilizing a survey research design, data were collected through structured questionnaires administered to a sample of 410 respondents. The findings reveal that two-way communication and the sponsorship of community development projects, such as schools, hospitals, and roads are the most prominent community relations strategies employed by public and private organizations in the region. These strategies have proven effective in strengthening the relationship between organizations and their host communities. The study concludes that community relations are essential in fostering mutual understanding and cooperation, thereby contributing significantly to rural development. It recommends that organizations adopt a participatory and two-way communication approach when designing and implementing community relations programs. Additionally, the sustainability and maintenance of community projects should be prioritized to preserve community trust. Finally, the study emphasizes that community relations should be proactive rather than reactive, aiming to prevent conflict and promote long-term, harmonious engagement between organizations and rural communities.